ANALISIS PELAKSANAAN DAN PERHITUNGAN KEBUTUHAN BETON PEKERJAAN KOLOM PADA PROYEK X CIBUBUR - Andi Asnur Pranata M. H; Uppit Yuliani; Ellysa Ellysa; Hermawan Tri Pambudi (Asosiasi Dosen Muda Indonesia, 2024)
The development of Project X Cibubur is located on Alternatif Cibubur Street, West Java. The project, which is built on a land area of ± 40100 m2, is a superblock in one area where there are malls, hotels, and apartments. The purpose of this research is to analyze and calculate the concrete demand for column work in Project X Cibubur. The type or form of column used in this project is square with several types of columns. The method of implementation carried out in column work includes preparation, measurement of axles, fabrication of reinforcement and formwork, transportation, installation, inspection, casting, dismantling formwork and maintenance. After calculating the volume of concrete requirements for column work, the total volume of concrete requirements for type K3A is 76.649 m3, K4A is 50.808 m3, K4B is 3.368 m3, and K4C is 3.334 m3. The total volume of concrete demand in column work is 134,159 m3.